2020
DOI: 10.1111/dth.14671
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy in cutaneous and genital warts: A review article

Abstract: Traditional treatment modalities for wart require long‐term treatment course and usually have high recurrence rates and unwanted side effects. In this review article, we evaluated different types of laser therapy in the treatment of warts. Published articles since 2000 up to July 2020 about laser therapy in genital and non‐genital warts were searched and assessed. Fifty articles were selected for the final review, including 22 pulsed dye laser (PDL), 10 neodymium‐yttrium‐aluminum‐garnet (Nd: YAG), 3 erbium‐dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 46 publications
0
33
0
3
Order By: Relevance
“…Existing wart treatments have low clearance rates and high recurrence rates, and as such, are increasingly seen as non-viable options for recalcitrant infections [17]. Licensed VLP-based HPV vaccines on the market target high-risk oncogenic HPV types, and while studies have reported limited positive responses against anogenital and cutaneous warts, their efficacy is hindered by a lack of specific coverage for verrucae-causing types, namely, HPV types 1, 2, and 3 [57, 58].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing wart treatments have low clearance rates and high recurrence rates, and as such, are increasingly seen as non-viable options for recalcitrant infections [17]. Licensed VLP-based HPV vaccines on the market target high-risk oncogenic HPV types, and while studies have reported limited positive responses against anogenital and cutaneous warts, their efficacy is hindered by a lack of specific coverage for verrucae-causing types, namely, HPV types 1, 2, and 3 [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven salicylic acid to be somewhat more effective than placebo [16]. Nonetheless, conventional treatments can be painful and inefficient, with low clearance rates and high recurrence rates [17]. Moreover, treatment has the potential to cause moderate to severe scarring, leading to severe deficits in cosmesis [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(18)(19)(20) Jika dibandingkan dengan terapi bedah listrik Clearance rate bisa mencapai 61-94% dan tingkat rekurensi mencapai 22 %, efek samping dan komplikasi yang muncul dapat berupa rasa nyeri setelah tindakan, timbulnya jaringan parut dan infeksi, maka dengan bedah laser CO2, (14,(18)(19)(20) luka infeksi lebih cepat sembuh dan hanya sedikit menimbulkan jaringan parut, serta angka rekurensi lebih rendah. (11,14,19,20) Edukasi tentang penyebab penyakitnya dan sumber penularanya melalui kontak seksual adalah hal sangat penting yang harus diberikan pada pasien. Baik penularan HIV dan HPV dapat disebabkan oleh perilaku seksual dan kedua penyakit ini sangat berkaitan erat bahkan menjadi faktor pendukung.…”
Section: Kasusunclassified